Parmenides as psychologist ”“ Part one: fragments DK 1 and 2 - Galgano, Nicola Stefano (Revista Archai, 2016)
The aim of this essay is to examine an aspect of Parmenides’ poem which is often overlooked: the psychological grounds Parmenides uses to construct his view. While it is widely recognized by scholars that following Parmenides’ view requires addressing mental activity, i.e. both the possibility of thinking the truth, as well as thinking along the wrong path that mortals follow, a closer examination of the psychological assumptions involved have, to my knowledge, not yet been attempted. I argue that by identifying and analyzing the psychological vocabulary in his poem, it is revealed that Parmenides was a keen observer of human mental behavior. Through these psychological (perhaps “cognitivist,” following some recent categories) observations of thought processes, Parmenides gains insight into the structure of thought itself. The outcome of this inquiry reveals three notable conclusions: First, the poem contains a remarkably extensive use of strictly psychological vocabulary. Second, the presence of this psychological material and the lack of scholarly attention to it means there is a significant aspect of Parmenides intellectual legacy that remains unexplored””Parmenides as psychologist, keen observer of human mental behavior. Furthermore, the recognition of this material helps shed important light on Parmenides’ philosophical message. Ultimately, I intend to provide an exhaustive treatment of Parmenides’ psychological language, which requires close examination of DK B 1, 2, 6, and 7. Due to spatial constraints, I have divided the inquiry into two parts, and will only address DK 1-2 below.